Inclusive Legal Communication for the Protection of the Rights of Persons with DisabilitiesA Comparative Study of Sweden, Canada, the Netherlands, Germany, and the United States - Ani Purwati; Gita Ruslita (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
The normative protection of the rights of persons with disabilities requires legal guarantees that go beyond formal recognition toward the realization of substantive rights. The legal orientation is directed toward ensuring accessibility to legal information, the provision of reasonable accommodation, and equal participation in public services. This normative framework is grounded in the principle of equality before the law and the prohibition of discrimination as affirmed in Articlen28D paragraph (1) and Article 28I paragraph (2) of the 1945 Constitution of the Republic of Indonesia. It is further reinforced by Law Number 8 of 2016 on Persons with Disabilities, particularly Article 24 concerning access to justice, as well as international commitments under the Convention on the Rights of Persons with Disabilities (CRPD), especially Article 9 on accessibility and Article 21 on access to information. At the empirical level, however, legal protection practices continue to demonstrate a discrepancy between norms and the implementation of public services. Limited access to information, the administrative character of legal communication, and institutional power asymmetries hinders the effective fulfilment of rights. This situation is exacerbated by the weak operational regulation of Article 24 of Law Number 8 of 2016, which has not yet comprehensively formulated standards for accessible legal communication. This study employs a normative juridical method with a comparative legal approach by examining legal communication practices in Sweden, Canada, the Netherlands, Germany, and the United States. The functional analysis indicates that the effectiveness of disability protection is largely determined by the integration of responsive legal norms with inclusive public communication systems. The study proposes a model of legal and communication reform that positions legal communication as a strategic instrument for rights protection through strengthening accessibility obligations, meaningful participation, and the reconstruction of power relations between the state and citizens with disabilities